2022
DOI: 10.1007/s40822-022-00206-8
|View full text |Cite
|
Sign up to set email alerts
|

Testing for asymmetric non-linear short- and long-run relationships between crypto-currencies and stock markets

Abstract: Using the NARDL model for the period of pandemic COVID19, we examined the asymmetric relationship between six crypto-currencies (Bitcoin, Litecoin, Bitcoin gold, Dash, Maker, and Ehereum) and seven stock market prices (S&P500, CAC40, DAX30, NIKKEI, FTSE, FTSEMIB, and SPTSX) accounting for the effects of Gold and WTI prices. In the long run, our results revealed, in most cases, a positive asymmetric relationship between digital and financial assets, suggesting a weak safe haven role for crypto-currencies. The o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 110 publications
(126 reference statements)
1
7
0
Order By: Relevance
“…Further, Sajeev and Afjal (2022) have investigated the contagion effect of Bitcoin on major global stock exchanges. Study findings suggest a weak time‐varying correlation and asymmetric volatility between the stock and Bitcoin markets (Ghorbel et al, 2022a). Similarly, Bianchi (2020) has found a mild correlation between traditional assets and cryptocurrency returns and documented no spillover effect between these asset classes.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 98%
See 2 more Smart Citations
“…Further, Sajeev and Afjal (2022) have investigated the contagion effect of Bitcoin on major global stock exchanges. Study findings suggest a weak time‐varying correlation and asymmetric volatility between the stock and Bitcoin markets (Ghorbel et al, 2022a). Similarly, Bianchi (2020) has found a mild correlation between traditional assets and cryptocurrency returns and documented no spillover effect between these asset classes.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 98%
“…The results are consistent with those of Kurka (2019) and Gil‐Alana et al (2020), which point out that the relationship between equity and digital currencies is insignificant but that the transmission of shock between them is significant. Meanwhile, some studies like Umar et al (2020), Sajeev and Afjal (2022), and Ghorbel et al (2022a) have demonstrated that stock prices often react to negative shocks in the cryptocurrency market more strongly than positive changes. Based on the above literature, we hypothesized that:…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“… Ghorbel et al, 2022 , Hemrit and Benlagha, 2021 , Kwon and Holliday, 2007 , Niu, 2021 , Awartani and Maghyereb, 2013 …”
Section: Uncited Referencesmentioning
confidence: 99%
“…In a study of the unidirectional causal relationship of cryptocurrencies with the COVID-19 pandemic, Toda and Yamamoto (linear) and Diks and Panchenko (nonlinear) Granger causality tests confirm the existence of unidirectional causality [ 7 ]. Ghorbel et al uncovered asymmetric correlations between the stock indexes and cryptocurrencies in both the short and long run and concluded that most stock prices respond more to the negative shocks of cryptocurrencies than to the positive ones [ 8 ]. Moreover, Tong et al examined cryptocurrency price volatility changes over time and are positively correlated.…”
Section: Introductionmentioning
confidence: 99%